Neither entrepreneurship nor intrapreneurship: a review of how to become an innovative split-off start-up - Knossalla, Christina Elisabeth; Carbon, Claus-Christian (Frontiers in Sociology, 2023)
Splitting off departments from corporations in order to establish corporate start-ups has become of strategic importance for the performance and innovation of corporations. While the settlement process is widely practiced, there is a lack of knowledge of how entrepreneurship may exist in such split-offs.The main aim of this study was to explore how entrepreneurship in corporate start-ups can exist in order to contribute to corporate performance. Based on a systematic literature review from 2021 to 2023, which resulted in a total of 1,516 scientific, English-language articles in economic journals, a total of 150 articles were analyzed in-depth. Our research shows that it is of crucial importance that corporations position leaders with an appropriate mindset and behavior at all levels as early as starting the split-off process, which is, however, neither entrepreneurship nor intrapreneurship. The niche corporative start-up area shows that entrepreneurship is a continuum and requires a new definition of corporate start-up entrepreneurship (CSE). For corporate start-ups to be successful, we revealed that there needs to be (1) the appropriate legal form, which ensures ownership but also the risk of the leaders, (2) an explorative business rather than exploitation, (3) variable compensation rather than fixed and (4) corporate entrepreneurs rather than employees and managers. Implications of the findings for entrepreneurial leadership theory development and future research are discussed.